Investigating the relationship between authentic leadership and athletes' commitment, positive affect, and perceived teammate prosocial behaviour via trust and team culture - Malloy, E.; Yukhymenko-Lescroart, M. A.; Kavussanu, M. (International Journal of Sports Science & Coaching, 2023)
Authentic leadership is a genuine form of leadership in which leaders demonstrate behaviours in line with their moral values. Research has started to examine this leadership style and its impact on a range of athlete outcomes. The aim of this study was to investigate whether coaches` authentic leadership, as perceived by their athletes, is related to athletes` commitment, positive affect and perceived teammate prosocial behaviour via trust and team culture. Participants were 366 (240 females, Mage = 21.07) athletes, participating mostly in team sports, who completed questionnaires assessing the aforementioned variables. Using multilevel path analysis, we found that authentic leadership was positively related to athletes' commitment and positive affect via trust and team culture, as well as to perceived teammate prosocial behaviour via trust. Our findings enhance our understanding of authentic leadership in sport and highlight its importance in predicting a range of outcomes. The findings suggest that authentic leadership in coaches could be key to creating more positive environments in sport.